The teacher will be very surprised to see your correct solution 😉

Detail solution

Given the linear equation:

Looking for similar summands in the left part:

Move the summands with the other variables

from left part to right part, we given:

$$- x = 19 y - 10$$

Divide both parts of the equation by -1

We get the answer: x = 10 - 19*y

-1*x-19*y = -10

Looking for similar summands in the left part:

-x - 19*y = -10

Move the summands with the other variables

from left part to right part, we given:

$$- x = 19 y - 10$$

Divide both parts of the equation by -1

x = -10 + 19*y / (-1)

We get the answer: x = 10 - 19*y

Rapid solution
[src]

x1 = 10 - 19*re(y) - 19*I*im(y)

$$x_{1} = - 19 \operatorname{re}{\left(y\right)} - 19 i \operatorname{im}{\left(y\right)} + 10$$

x1 = -19*re(y) - 19*i*im(y) + 10